Surgical explantation of transcatheter aortic bioprosthesis: A systematic review and meta-analysisCentral MessagePerspective - Yujiro Yokoyama, MD; Toshiki Kuno, MD, PhD; Syed Zaid, MD; Tsuyoshi Kaneko, MD; Hisato Takagi, MD, PhD; Gilbert H.L. Tang, MD, MSc, MBA; Shinichi Fukuhara, MD (JTCVS Open, 2021)
Background: Despite the rapid adoption of transcatheter aortic valve replacement (TAVR), aortic valve reintervention, particularly surgical TAVR valve explantation (TAVR explant), has not been well described. Methods: MEDLINE, Embase, and Web of Science were searched through July 2021 to identify observational studies and case series reporting clinical outcomes of TAVR explant. Data on the frequency of TAVR explant, patient demographic characteristics, clinical indications, operative data, and perioperative outcomes were extracted. Study-specific estimates were combined using one-group meta-analysis in a random-effects model. Results: A total of 10 studies were identified that included 1690 patients undergoing a TAVR explant. The frequency of TAVR explant among TAVR recipients was 0.4% (95% confidence interval [CI], 0.2%-0.6%). The mean patient age was 73.7 years (95% CI, 72.9-74.6 years). The mean Society of Thoracic Surgeons predicted risk of mortality was 5.9% (95% CI, 2.9%-8.8%) at the index TAVR and 8.1% (95% CI, 5.4%-10.8%) at TAVR explant. The mean time from implant to explant was 345.0 days (95% CI, 196.7-493.3 days). Among patients with documented device type, 59.8% (95% CI, 43.5%-76.0%) had a balloon-expandable valve and 40.2% (95% CI, 24.0%-56.5%) had a self-expandable valve. Concomitant procedures during TAVR explant were performed in 52.9% of patients (95% CI, 33.8%-72.0%), and the most common concomitant procedure was aortic repair (28.5%; 95% CI, 14.0%-42.9%). The 30-day mortality after TAVR explant was 16.7% (95% CI, 12.2%-21.2%). Conclusions: TAVR explant in patients with a failing TAVR appears to be rare; however, the clinical impact of TAVR explant is substantial. Implanters must be mindful of the need for a lifetime management strategy in younger and lower-risk patients when choosing the valve type for the initial procedure.